Study of Replication of Mumps Virus in Cell Culture By Hemadsorpsiyon and Imunoperoxidase Assays - Bulut, Yasemin; Bulut, Hakan; Özdarandeli, Aykut (Fırat University, 2002)
Aim: Aim of this study was to investigate the replication of mumps virus (MuV) in Vero cells by two different assays. Material and Methods: In the study, hemadsorption and immunoperoxidase assays in various times of infection were performed in the MuV infected cells. Results: In this study, first hemadsorpsition at surface of the infected cells was detected in 12 h of post infection (p.i.). Formation of syncytia foci, which are known to be formed by MuV fusion proteins in cellular membranes, was detected after 22 h p.i. Specificity of MuV of this cytopati effects was shown by immunoperoxidase assay. Conclusion: The results of present study indicated that the heamaglutinin-neuraminidase protein of MuV was appeared in early period of infection, but fusion protein was synthesized during late period of infection.

Amaç: Bu çalışmanın amacı, Vero hücrelerinde kabakulak virüs (mumps virüs; MuV) replikasyon kinetiğinin iki farklı deney ile araştırılmasıdır. Gereç ve Yöntem: Çalışmada, MuV ile infekte hücrelerde, infeksiyonun farklı saatlerinde hemadsorpsiyon ve immunoproksidaz deneyleri gerçekleştirilmiştir. Bulgular: Çalışmada, infekte hücre yüzeylerinde ilk hemadsorpsiyon infeksiyonun 12. saatinde belirlenmiştir. İnfeksiyondan 22 saat sonra ise, infekte hücre membranlarında bulunan MuV'ın füzyon proteininin şekillendirdiği bilinen sinsişyal odaklar görülmeye başlamıştır. İmmunoperoksidaz deney neticesinde, bu sitopatik odakların MuV'a özgüllüğü gösterilmiştir. Sonuç: Çalışmanın bulguları, infeksiyonun erken saatinde MuV'ın hemaglütinin-nöraminidaz proteinini sentezlediğini göstermektedir.
Hücre Kültüründe Kabakulak Virüs Replikasyonunun Hemadsorpsiyon ve İmmunoperoksidaz Deneyleriyle Çalışılması